2000
DOI: 10.1038/35018092
|View full text |Cite
|
Sign up to set email alerts
|

A sphingosine-1-phosphate receptor regulates cell migration during vertebrate heart development

Abstract: Coordinated cell migration is essential in many fundamental biological processes including embryonic development, organogenesis, wound healing and the immune response. During organogenesis, groups of cells are directed to specific locations within the embryo. Here we show that the zebrafish miles apart (mil) mutation specifically affects the migration of the heart precursors to the midline. We found that mutant cells transplanted into a wild-type embryo migrate normally and that wild-type cells in a mutant emb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
295
0
3

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 384 publications
(309 citation statements)
references
References 26 publications
11
295
0
3
Order By: Relevance
“…At the 19-somite stage, cardiac fusion is under way in the wild-type embryo, but the myocardiocytes in the mil mutant embryo have not moved to the midline. As shown above for cas, these cells will remain in bilateral positions (Kupperman et al, 2000).…”
Section: What Drives Cardiac Fusion?mentioning
confidence: 78%
See 1 more Smart Citation
“…At the 19-somite stage, cardiac fusion is under way in the wild-type embryo, but the myocardiocytes in the mil mutant embryo have not moved to the midline. As shown above for cas, these cells will remain in bilateral positions (Kupperman et al, 2000).…”
Section: What Drives Cardiac Fusion?mentioning
confidence: 78%
“…The precise nature of this signal is not yet known. However, generation or reception of this signal seems to involve the function of miles apart (mil), which encodes a lysosphingolipid G-protein-coupled receptor (Kupperman et al, 2000). Mutation of mil causes cardia bifida without disrupting gut formation or myocardial differentiation (Fig.…”
Section: What Drives Cardiac Fusion?mentioning
confidence: 99%
“…Although these two genes appear to have diverged early in phylogeny, the similarity of the cis-elements that drive their expression in the developing heart seems to have been maintained. It is noteworthy that, in zebrafish, a mutation in S1p 2 called miles apart results in fusion of the bilateral heart tubes, or cardia bifida (Kupperman et al, 2000); the analogous phenotype is not observed in S1p 2 -null mice , suggesting that multiple members of the LPA/S1P receptor family likely contribute to heart morphogenesis in these species.…”
Section: Correlation Between the Phylogenetic Relationship Of Membersmentioning
confidence: 99%
“…S1P 2 receptor-null mice are apparently normal at birth, with no anatomical defects, but between weeks 3 and 7, 59% of them are affected by sporadic seizures that are occasionally lethal (14% die) [180]. Interestingly, a mutation in a similar gene in zebrafish leads to embryonic lethality [181]. Therefore S1P 2 receptors could affect either microscopic development or membrane excitability by affecting intracellular calcium.…”
Section: Overview Of S1p Family Of Receptorsmentioning
confidence: 99%